2011
DOI: 10.1111/j.1440-1630.2011.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy students’ contribution to occasions of service during practice placements in health settings

Abstract: A novel method for reporting productivity and time-use changes during clinical education programs for occupational therapy has been applied. Supervisors spent considerable time in assessing and managing students and their clinical education role should be seen as core business in standard occupational therapy practice. This paper will contribute to future assessments of the economic impact of student placements for allied health disciplines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
0
20
2
Order By: Relevance
“…Not surprisingly, student OOS increased across Weeks 1-5 of the placement block. This is in contrast with findings in previous studies, 8,13 where no change in OOS during clinical placements was reported for the student-supervisor team in the case of occupational therapy and dietetic students. Although the differences were not statistically significant, Rodger et al 13 demonstrated that the number of OOS had periods of growth during placements of longer length (10-14 weeks), with the main growth occurring between Weeks 1 and 3.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, student OOS increased across Weeks 1-5 of the placement block. This is in contrast with findings in previous studies, 8,13 where no change in OOS during clinical placements was reported for the student-supervisor team in the case of occupational therapy and dietetic students. Although the differences were not statistically significant, Rodger et al 13 demonstrated that the number of OOS had periods of growth during placements of longer length (10-14 weeks), with the main growth occurring between Weeks 1 and 3.…”
Section: Discussioncontrasting
confidence: 99%
“…Clinical educator (CE) and student occasions of service (OOS) and time spent treating patients have been measured, with comparisons made before, during and after student clinical placements. 7,8 However, to date, no study has investigated the volume of, or changes in, physiotherapy student OOS or length of OOS (LOOS; treatment time) throughout a clinical placement across different clinical areas. Another factor that may affect student contribution is the CE : student ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Each survey tool comprised three components, with the time‐use survey component informed by the approach used by Rodger et al . (). The three parts of the survey were as follows: Background information form: captured demographic information deemed by the research team to be related to the study questions.…”
Section: Methodsmentioning
confidence: 97%
“…In the case of the latter, there is much still to learn (Rodger et al . , Ozelie et al . , Sevenhuysen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation